Lexical Density in The Novel “Mrs. Dalloway” by Virgina Woolf - Salma Nurmala Ayu; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Discourse analysis studies how sentences and utterances (speech) combine to form texts and interactions and how those texts and interactions fit into our everyday sphere (Jones, 2012). This study aims to measure the lexical density in The Novel “Mrs. Dalloway” by Virgina Woolf. Descriptive qualitative were used to conduct the study. The data were taken by collecting and identifying the lexical items in that novel and then calculating the lexical density in the novel Mrs. Dalloway. A novel is a literary work that reflects a story about a specific human experience with a certain length, including a complex plot, a variety of settings, and several characters (Soemardjo, 1989). The result of this research from 10 Data was obtained that the lexical density of this research was reaching (51%).  The lexical items or content words found in this study were: noun 22 (40%), verb 13 (23,6%), adverb 8 (14,6%), adjective 12 (21,8%), and the highest lexical density was noun standing for (40%).